Cirrhotic Patients Admitted to the ICU With Septic Shock: Factors Predicting Short and Long-Term Outcome. Issue 4 (October 2019) - Baudry, Thomas; Hernu, Romain; Valleix, Baptiste; Jahandiez, Vincent; Faucher, Etienne; Simon, Marie; Cour, Martin; Argaud, Laurent
Abstract : ABSTRACT: Cirrhotic patients with septic shock have a poor prognosis in ICU compared to general population of critically ill patients. Little is known about long-term outcome in these patients. We performed a retrospective analysis of a prospective cohort of cirrhotic patients with septic shock. The aim of this study was to describe both short and long-term outcomes and to evaluate factors predicting mortality. Data from 149 patients were analyzed (mean age: 60 ± 11 years, sex ratio: 2.4). Mortality rate in the ICU was 54% and at 1 year it was 73%. Among factors associated with adverse outcome, independent factors predicting ICU mortality were early need for renal replacement therapy (odds ratios, OR 13.95, 95% confidence interval, CI 3.30; 59.03) and arterial lactate >5 mmol.L −1 (OR 7.27, 95% CI 2.92; 18.10), and early use of mechanical ventilation (OR 3.05, 95% CI 1.08; 8.58). For 1-year mortality, independent prognostic factors were the need for renal replacement therapy during ICU stay (OR 9.60, 95% CI 2.90; 31.82), prothrombin time ⩽40% (OR 3.47, 95% CI 1.43; 8.43), and Charlson score (OR 1.36 per point, 95% CI 1.11; 1.67). The results emphasize the poor prognosis of cirrhotic patients with septic shock admitted to the ICU. The need for organ supports appears to be a better predictor of short-term outcome than the underlying hepatic disease. Renal replacement therapy is associated with both short and long-term outcomes. Abstract : Supplemental Digital Content is available in the text